2001
DOI: 10.1002/poc.414
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pure non‐ionic and mixed non‐ionic–cationic surfactants on the rates of hydrolysis of phenyl salicylate and phenyl benzoate in alkaline medium

Abstract: The pseudo-first-order rate constants (k obs ) for the alkaline hydrolysis of phenyl benzoate (PB) decrease monotonically from 72.0 Â 10 À4 to 7.4 Â 10 À4 s À1 with increase in the concentration of polyoxyethylene 23 lauryl ether ([C 12 E 23 ] T ) from 0.0 to 0.01 M at 0.01 M NaOH and 35°C. The results fit satisfactorily to a pseudophase model of micelles. The values of k obs for the hydrolysis of ionized phenyl salicylate (PS À ) are almost independent of [C 12 E 23 ] T within the range 0.0-0.02 M at 0.01 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…It has been observed that an increase in the total concentration of cetyltrimethylammonium bromide ([CTABr] T ) from 0.0 to 0.03 M has no effect on the apparent pK a of the conjugate acid of 4 in the presence of 0.02 M C 12 E 23 [15], which is considered to be unusual in view of our understanding (through pseudophase ion exchange model of micelle) of the occurrence of ion exchange of HO À /Br À at CTABr micellar surface [16][17][18]. The observed kinetic data (k obs vs. [C m E n ] T ), reported in earlier studies [9][10][11][12][13][14][15], failed to obey PM model at greater than the typical values of R t (=[C m E n ] T /[HO À ] T ). The plausible reason(s) for such observations remained unknown.…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…It has been observed that an increase in the total concentration of cetyltrimethylammonium bromide ([CTABr] T ) from 0.0 to 0.03 M has no effect on the apparent pK a of the conjugate acid of 4 in the presence of 0.02 M C 12 E 23 [15], which is considered to be unusual in view of our understanding (through pseudophase ion exchange model of micelle) of the occurrence of ion exchange of HO À /Br À at CTABr micellar surface [16][17][18]. The observed kinetic data (k obs vs. [C m E n ] T ), reported in earlier studies [9][10][11][12][13][14][15], failed to obey PM model at greater than the typical values of R t (=[C m E n ] T /[HO À ] T ). The plausible reason(s) for such observations remained unknown.…”
Section: Introductionmentioning
confidence: 58%
“…But the values of R t were 88 and $5 at respective 1.0 and 0.76 mM NaOH for C 16 E 10 as well as 140 at 1.0 mM NaOH for C 16 E 20 [12]. In all these studies [9][10][11][12], the observed data, obtained at R < R t , have been explained in terms of PM model. The unusual near irreversible trapping of moderately hydrophobic reactants by C m E n micelles at R P R t cannot be attributed to the usual shielding effect of micelles [12].…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations